Possibilities of Magnetic Resonance Imaging of the Brain in Infantile Cerebral Palsy - Anna N. Belova; Gennadii E. Sheiko; Evgenii А. Klyuev; Maksim G. Dunaev (Вопросы современной педиатрии)
Infantile cerebral palsy (ICP) is the main cause of childhood disability and is characterized by a non-progressive lesion and/or impaired development of the brain in a foetus or newborn. Magnetic resonance imaging (MRI) is a modern non-invasive method with extensive capabilities for diagnosing brain damage in ICP. The review focuses on anatomical structural MR patterns of brain damage in ICP and gives the present-day classification of MR changes in this disease. The role of MRI in determining the duration of brain damage in ICP has been considered. Data on the ratio of ICP phenotypes to pathological MR findings has been presented. Neuroimaging prognostic biomarkers are discussed. It is emphasized that many questions regarding the prognostic significance of MR findings remain unresolved; prospects are associated with the use of new MRI modalities such as functional and diffusiontensor MRI.